Validity and reliability of the Turkish version of the emotional communication in hearing questionnaire - BAL, NİLÜFER (My University, 2023)
Purpose: The Emotional Communication in Hearing Questionnaire (EMO-CHeQ) is designed to evaluate awareness of vocal emotion information and perception of emotion. This study sought to translate the EMO-CHeQ into Turkish in accordance with international standards and to ascertain its validity and reliability statistically by administering it to native Turkish-speaking subjects. Method: This empirical study involved collecting data from participants using a scale. A total of 460 individuals, comprising 158 women and 302 men (Mage = 33.43 ± 13.14 years), participated. The data encompassed 295 subjects with normal hearing, 101 hearing aid users, and 64 cochlear implant users. Exploratory factor analysis, followed by confirmatory factor analysis, was employed to ensure construct validity. Internal consistency was assessed with Cronbach's alpha reliability analysis, and content validity was applied to examine how effectively the Turkish version of the scale fulfilled its intended purpose. Results: The total Cronbach's alpha internal consistency coefficient of the scale was .949, and the explained variance was 74.385%. The Turkish version of the EMO-CHeQ demonstrated high construct validity, internal consistency, and explanatory efficacy. The scale revealed significant differences (p < .05) in emotional communication among the normal-hearing group, hearing aid users, and cochlear implant users. Conclusions: The Turkish adaptation of the EMO-CHeQ is a credible and robust tool for evaluating how individuals perceive emotion in speech. Emotion perception was found to be suboptimal among hearing aid users compared to cochlear implant users, although it was most proficient in those with normal hearing.